Positive impact of social relationships fostered by physical and/or cognitive group activity on older people’s quality of life: PRISMA systematic review - Gonnord, Tiphanie; Clarys, David; Boucard, Geoffroy; Esnard, Catherine (Frontiers in Psychology, 2023)
Introduction: This review identified and examined the research literature on the effect of participating in physical and/or cognitive activities on older people's quality of life, to establish whether the social relationships fostered by these activities can be a vector of better physical, mental and social quality of life.Method: A systematic review of the literature was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched four databases (MEDLINE, APA PsycArticles/PsycInfo, PubMed, and Web of Science) for articles published between 1975 and 2022 using search terms related to psychosocial, population, and intervention topics. Studies were eligible if they involved older adults, participation in at least one activity (physical or cognitive), and at least one quality of life related outcome measure.We selected 20 articles published between 1990 and 2021, the majority concerning studies conducted in English-speaking countries. Ten studies were interventional (introduction of program of activities), and 10 studies were observational (60% quantitative, 40% qualitative). Overall, results revealed a positive impact of the activities on every aspect of quality of life (i.e. cognitive, physical, social, psychological, and quality of life in general).The present review confirmed the beneficial impact of practicing physical and/or cognitive group activities on older people's quality of life, but the contribution of social factors and social relationships remains underestimated and not well defined in researches.